2023
DOI: 10.3174/ajnr.a7847
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation Evoked by Motor Imagery in Pediatric Patients with Complete Spinal Cord Injury

Abstract: BACKGROUND AND PURPOSE: Currently, there is no effective treatment for pediatric patients with complete spinal cord injury. Motor imagery has been proposed as an alternative to physical training for patients who are unable to move voluntarily. Our aim was to reveal the potential mechanism of motor imagery in the rehabilitation of pediatric complete spinal cord injury.MATERIALS AND METHODS: Twenty-six pediatric patients with complete spinal cord injury and 26 age-and sex-matched healthy children as healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This activation may lead to enhancements in motor function, muscle strength, and spasticity, as demonstrated by studies conducted by Opsommer et al [25]. Furthermore, motor imagery interventions can augment body awareness, stimulate neuroplasticity, and expedite the integration of prosthetic devices or assistive technologies [26,27].…”
Section: Spinal Cord Injurymentioning
confidence: 98%
“…This activation may lead to enhancements in motor function, muscle strength, and spasticity, as demonstrated by studies conducted by Opsommer et al [25]. Furthermore, motor imagery interventions can augment body awareness, stimulate neuroplasticity, and expedite the integration of prosthetic devices or assistive technologies [26,27].…”
Section: Spinal Cord Injurymentioning
confidence: 98%
“…Rienzo et al [186] found that after adding MI training to the rehabilitation program of patients with SCI, the activation of compensatory brain areas decreased, and the cortical activity was closer to the normal state, suggesting that MI training partially reversed the compensatory neural activation in patients with SCI, which was beneficial to the integration of normal neural networks. The latest study by Wang et al [187] compared the effect of MI in children with SCI with that in healthy subjects by fMRI. The results showed that the activation degrees of bilateral paracentral lobules, auxiliary motor area, putamen, and cerebellar lobules in patients with SCI were higher than those in healthy ones.…”
Section: Motor Imagination Rehabilitation Regulates the Brainmentioning
confidence: 99%
“… 11 , 12 Similar to adult CSCI patients, the brain reorganization caused by the interruption of ascending and descending conduction pathways has been demonstrated to be a critical factor affecting the sensory motor rehabilitation of pediatric CSCI patients. 13 , 14 Nevertheless, it remains currently unclear whether there have been changes in the brain regions related to cognitive, emotional, or other functions after CSCI. Clarifying the changes in cerebral cortex and deep GM nuclei of children after CSCI may provide a possible neural basis for the cognitive‐emotional or other disorders beyond the sensory motor disabilities, and guide relevant early intervention treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that pediatric CSCI always presents many other physiological and psychological abnormalities, such as cognitive, emotional, behavioral, or other disorders, in addition to sensory motor dysfunction 11,12 . Similar to adult CSCI patients, the brain reorganization caused by the interruption of ascending and descending conduction pathways has been demonstrated to be a critical factor affecting the sensory motor rehabilitation of pediatric CSCI patients 13,14 . Nevertheless, it remains currently unclear whether there have been changes in the brain regions related to cognitive, emotional, or other functions after CSCI.…”
Section: Introductionmentioning
confidence: 99%